ADAM SMITH ON JUSTICE, SOCIAL JUSTICE, AND ULTIMATE JUSTICE. Issue 1 (14th June 2017) - Otteson, James R.
Abstract: Adam Smith argues that virtue falls into two broad categories: "justice, " which he calls a "negative" virtue because it principally comprises restraint from harming or injuring others; and "beneficence, " which he calls "positive" because it comprises the actions we ought to take to improve others' situations. Smith's conception of justice is thus quite "thin, " and some critics argue that it is indeed too thin, since it fails to incorporate substantive concerns for the well-being of others. In this essay, I lay out Smith's conception of justice and offer a way to understand it that attempts to comprehend the various things he says about it. I then offer a cluster of objections drawing on criticisms that might fall under the heading of "social justice." Finally, I suggest how Smith might respond to the criticisms by outlining a Smithian conception of what I call "ultimate justice."